2019
DOI: 10.1039/c9nr05279h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic stripes and transport properties in borophene heterostructures

Abstract: We performed a theoretical investigation of the structural and electronic properties of (i) pristine, and (ii) superlattice structures of borophene. In (i), by combining first-principles calculations, based on the density functional theory (DFT), and simulations of the X-ray Absorption Near-Edge Structure (XANES) we present a comprehensive picture connecting the atomic arrangement of borophene and the X-ray absorption spectra. Once we have characterized the electronic properties of the pristine systems, we nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…The 2D boron polymorphs observed experimentally are all metallic in character, which is consistent with multiple computational studies. ,,,, A potential exception is the α sheet (ν 1/9 ), which Wu et al calculated to be a narrow bandgap semiconductor, but the experimental observation of this structure requires further investigation . In a study by Silvestre et al, the ν 0 structure was found to exhibit a more anisotropic band structure than the ν 1/6 and ν 1/5 structures . Additionally, the authors found that the π* states in the ν 1/6 structure are more localized than in the ν 1/5 structure.…”
Section: Elemental 2d Materialssupporting
confidence: 75%
See 4 more Smart Citations
“…The 2D boron polymorphs observed experimentally are all metallic in character, which is consistent with multiple computational studies. ,,,, A potential exception is the α sheet (ν 1/9 ), which Wu et al calculated to be a narrow bandgap semiconductor, but the experimental observation of this structure requires further investigation . In a study by Silvestre et al, the ν 0 structure was found to exhibit a more anisotropic band structure than the ν 1/6 and ν 1/5 structures . Additionally, the authors found that the π* states in the ν 1/6 structure are more localized than in the ν 1/5 structure.…”
Section: Elemental 2d Materialssupporting
confidence: 75%
“…Furthermore, multiple studies report the coexistence of the ν 1/6 and ν 1/5 structures, attesting to the polymorphism of borophene. ,,, An STM image of a region containing intermixed ν 1/6 and ν 1/5 domains is presented in Figure b. As suggested by Silvestre et al, the formation of periodically alternating domains of the ν 1/6 and ν 1/5 phases could be leveraged to form electronic stripes or transport channels …”
Section: Elemental 2d Materialsmentioning
confidence: 75%
See 3 more Smart Citations